"Candidatus Neoehrlichia chilensis" sp. nov.: Molecular detection and characterization of a novel Anaplasmataceae in wild rodents from Valdivia, southern Chile. Issue 2 (24th January 2018) - Müller, A.; Monti, G.; Otth, C.; Sepúlveda, P.; Bittencourt, P.; Nachum‐Biala, Y.; Gutiérrez, R.; Harrus, S.
Summary: This study aimed to screen wild rodents from southern Chile, for the presence of Anaplasmatacea. Spleen samples from 33 wild rodents trapped in Valdivia Province were screened by conventional PCR (cPCR), targeting the Anaplasmataceae 16S rRNA gene (16S). Positive samples were further evaluated, targeting a larger 16S fragment, groEL operon, and gltA gene, followed by sequencing and phylogenetic analysis. Anaplasmataceae DNA was detected in 15% (five of 33) of the tested rodents ( Abrothrix sp. [four of five] and Mus musculus [one of five]). Analysis of sequenced products based on the 16S gene revealed high similarity with " Ca . Neoehrlichia mikurensis, " " Ca . Neoehrlichia lotoris" and " Ca . Neoehrlichia arcana" (97.8%–98.6%). A lower similarity was observed with Candidatus Neoehrlichia groEL (89.7%‐92%) and gltA (79.5%–79.9%) loci. According to the 16SrRNA, groEL and gltA phylogenetic analyses, two closely related genotypes of " Candidatus Neoehrlichia" spp. from Chile were observed, which clustered together in a separate clade from other species in this genus. This study suggests the presence of two genotypes of a novel species of " Candidatus Neoehrlichia, " proposed as " Candidatus Neoehrlichia chilensis, " circulating in rodents from Chile. This is the first report of " Ca . Neoehrlichia" species in rodents from America.